2012
DOI: 10.1597/11-030
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Orthopedics Has No Effect on Archform in Unilateral Cleft Lip and Palate

Abstract: There was no evidence that presurgical orthopedics produced any significant effect on archform, raising questions for its continued use in this context. Lip repair had a greater impact on arch dimensions than did presurgical orthopedics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 46 publications
1
31
0
4
Order By: Relevance
“…A similar phenomenon was observed by Huang et al (2002), who stated that the angular measurements (GC-CC′, GIC) indicated palatal displacement of the frontal part of the nonclefted segment and the continuous reduction of both angles. The reduction of angles is caused by the molding effect of the lip reconstruction which contributes to the formation and symmetry of the dentoalveolar arch (Eichhorn et al, 2011; Adali et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon was observed by Huang et al (2002), who stated that the angular measurements (GC-CC′, GIC) indicated palatal displacement of the frontal part of the nonclefted segment and the continuous reduction of both angles. The reduction of angles is caused by the molding effect of the lip reconstruction which contributes to the formation and symmetry of the dentoalveolar arch (Eichhorn et al, 2011; Adali et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…[93,95] Similarly, Adali et al, 2012 reported that PSO had no significant effect on arch dimensions. [96] Uzel and Alparslan, 2011 reported long-term effects of PSIO appliances with respect to treatment outcomes from a systematic review to assess the scientific evidence for the same in patients with cleft lip and palate. In their study, it was found that seven randomized controlled trials (Dutchcleft) assessed different treatment outcomes at different ages for a maximum follow-up of 6 years, where they observed no positive effects on feeding, speech, arch dimensions, facial growth, occlusion and nasolabial appearance using passive plates.…”
Section: Discussionmentioning
confidence: 99%
“…12 Based on findings by retrospective studies, some authors see advantages of PSO therapy in terms of narrowing the cleft width, thereby facilitating subsequent surgery. 8 In contrast, other authors found no alteration of maxillary alveolar ridge shape in CLP subjects treated with PSO compared with a nontreated control group, while surgical correction of cleft lips seemed to have a greater impact on arch dimensions than did PSO.…”
Section: Potential Benefits Of Psomentioning
confidence: 99%
“…8 In contrast, other authors found no alteration of maxillary alveolar ridge shape in CLP subjects treated with PSO compared with a nontreated control group, while surgical correction of cleft lips seemed to have a greater impact on arch dimensions than did PSO. 12 PSO is often reasoned by the postulate that the tongue of CLP newborns needs to be trained to maintain a posture considered to be physiological in order to support normal language development: Based on sonography analyses of tongue movements and postoperative articulatory function in CLP children aged about 5 years, Suzuki et al concluded that those subjects could not create negative pressure in the oral cavity, regardless of previous presence or absence of an orthopedic plate. 25 This finding is confirmed by the results of our study (Table 3).…”
Section: Potential Benefits Of Psomentioning
confidence: 99%
See 1 more Smart Citation